The impact of AIDS psychological and social aspects of HIV infection / edited by Jose Catalan, Lorraine Sherr, Barbara Hedge. - Catalan, Jose; Sherr, Lorraine; Hedge, Barbara (Harwood Academic Pub., 1997)
From the start of the HIV epidemic, the psychological and social aspects of the AIDS infection have been recognized. This volume contains a selection of key contributions to the discussion on the psychological and social implications of such infection